2006
DOI: 10.3347/kjp.2006.44.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel Leishmania major antigens that elicit IgG2a response in resistant and susceptible mice

Abstract: Experimental murine models with high, intermediate and low levels of genetically based susceptibility to Leishmania major infection reproduce almost entire spectrum of clinical manifestations of the human disease. There are increasing non-comparative studies on immune responses against isolated antigens of L. major in different murine strains. The aim of the present study was to find out whether there is an antigen that can induce protective immune response in resistant and susceptible murine strains. To do th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Although it is generally accepted that the Th2 cytokine IL-4 contributes to the generation of antigen specific IgG1 antibodies, other cytokines (Bryson et al, 2008) and parasite derived factors (Buxbaum, 2013; Mohammadi et al, 2006) have been shown to affect IgG subclass distribution. Moreover, levels of IgG1 and IgG2a antibodies do not always correlate with disease outcome (Fossati-Jimack et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is generally accepted that the Th2 cytokine IL-4 contributes to the generation of antigen specific IgG1 antibodies, other cytokines (Bryson et al, 2008) and parasite derived factors (Buxbaum, 2013; Mohammadi et al, 2006) have been shown to affect IgG subclass distribution. Moreover, levels of IgG1 and IgG2a antibodies do not always correlate with disease outcome (Fossati-Jimack et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that 152 and 140 kDa proteins from the L. major promastigotes were capable to induce antibodies of the IgG2a isotype in both susceptible and resistant mice (Mohammadi et al, 2006). In the present study, we made attempts to purify these 2 recently detected novel antigens from L. major pro- (Fig.…”
mentioning
confidence: 76%
“…Previously we have shown that 2 novel antigens from L. major promastigotes in the late log-phase of growth are capable to induce antibodies of the IgG2a isotype in both resistant and susceptible mice (Mohammadi et al, 2006). The goal of the current study is to localize and further characterize these novel antigens.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In leishmaniasis, resistance and resolution of the illness have been associated with IgG2a production (Mohammadi et al, 2006) and activation of Th1 cells with secretion of IL-2 and IFN-γ. In mice, IL-4 secreted by Th2 cells induces an immunoglobulin isotype switch on B lymphocytes to IgG1 and IgE, whereas IFN-γ produced by Th1 clones increased the response of the IgG2a isotype (Stavnezer, 1996).…”
Section: Discussionmentioning
confidence: 99%